Study the effect of some environmental factorial and chemical pesticides on different stages of Dubas bugs Ommatissus binotatus lybicus Deberg. on two categories of the Date palm Phoenix dactylifera L. under field conditions. - Al-Sweedi, Taha M. Mohammed (Journal of Kerbala for Agricultural Sciences, 2016)
The date palm Phoenix dactylifera L. is infected by many insects and non-insect pests in Iraq. One of the major pests of palm trees is Dubas Bugs Ommatissus binotatus lybicus Deberg. . This study was carried out in two orchards in terms of Albahadlah - the holy city of Kerbala (the distance between them is about 3 kilometers ) for the period from 09/01/2013 up to 03/04/2014 to study the effect of temperature and relative humidity levels as well as insecticides (plant extracts) Thiamethoxan WC and Alphacypermethrin EC on numerical density of the number of eggs and movable stages (nymphs and adults) as well as on the percentage of male and female Dubas on the palm of the two categories Zahadi and Khstawe on field conditions. The results showed an increase numerical density when the average temperature is between 25-33 C° and relative humidity between 30-50% and the heavy torrential rains during the implementation of this study impact in reducing the population density of the instars of moving the insect did not eggs developed by former female preparation affected. The absence of significant differences between the preparation of movable instars rates and the number of eggs for the two categories Zahdi and Khstawe It was noted, but there were significant differences between female adult insect for two classes Zahdi and Khstawe if the overall rate of female adults is 2.26,2.48 Females / 5 Pinnaes / Palm / week for two classes Zahdi and Khstawe ,respectively and the total rate of male adults is 1.86,2.14 Males / 5 Pinnaes / Palm / week for two classes Zahdi and Khstawe ,respectively . As well as the results showed the existence of significant differences between the effect of pesticides on the overall rate of live stages of the two categories Zahdi and Khstawe and the presence of significant differences dead stages is 4.56 insects / Pinnae of the variety and ascetic 3.26 insects / 10 pinnaes. When the percentage of the effectiveness of insecticides account and found that the percentage of the effectiveness of Alphacypermethin was 19.34% and for Thiamethoxan is 40.78% and the latter was more the effect of the pesticide after 24,48 and 72 hours of control. The decline in the percentage of females and males before control, as was 64.58% for females and 35.42% for males of the variety Zahdi and 59.61% for females and 40.31% for males of the variety Khstawe for increase after the fight, as was 48.26% of females and 26.04% for males of the variety Zahdi and 45.24% for females and 29 0.51% for males of the variety Khstawe. The results of the effect of insecticides on the population density of the number of eggs did not record any significant differences evident between times beyond control but they differ significantly on the number of eggs living and the dead by the control.